1995
DOI: 10.1056/nejm199510053331402
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Asthma — Bronchial Hyperresponsiveness Coinherited with a Major Gene for Atopy

Abstract: This study demonstrates that a trait for an elevated level of serum total IgE is coinherited with a trait for bronchial hyperresponsiveness and that a gene governing bronchial hyperresponsiveness is located near a major locus that regulates serum IgE levels on chromosome 5q. These findings are consistent with the existence of one or more genes on chromosome 5q31-q33 causing susceptibility to asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
389
1
15

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 720 publications
(425 citation statements)
references
References 44 publications
20
389
1
15
Order By: Relevance
“…Chromosome 5q31-q33 is linked to atopy and/or asthma and bronchial hyper-responsiveness. 8,[22][23][24][25][26][27][28] Thus, the weak but positive findings of linkage to 5q33 in the present study may reflect one of the loci common to asthma and SAR.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Chromosome 5q31-q33 is linked to atopy and/or asthma and bronchial hyper-responsiveness. 8,[22][23][24][25][26][27][28] Thus, the weak but positive findings of linkage to 5q33 in the present study may reflect one of the loci common to asthma and SAR.…”
Section: Discussionmentioning
confidence: 48%
“…Linkage of atopy and total serum IgE levels to chromosome 5q31-q33 and 12q24 has been reported. 8,[22][23][24][25][26][27][28][29] Weak linkage of asthma to chromosome 3p24 was also reported in the Hutterites. 6 Suggestive evidence for linkage of specific IgE against OG to 4p16.1, 11q14.3, and 16p12.3 was observed in the present study.…”
Section: Discussionmentioning
confidence: 80%
“…Beyer et al 35 found evidence for linkage and allelic association with atopic dermatitis (AD) on chromosomes 13q12-14 and 5q31-33. The marker D5S436 on chromosome 5q31-33, which showed evidence for association with AD in the study by Beyer et al, 35 was the same marker associated with bronchial hyperresponsiveness and atopy in a study by Postma et al 36 Spergel and Paller 19 postulated that epicutaneous sensitization in AD arises from exposure of the damaged skin to potential allergens. They suggested that such sensitization is followed by migration of T H 2 memory cells from the skin to the bronchusassociated lymphoid tissue and that subsequent inhalation of the sensitizing allergen causes a cellular and humoral response in the airways, resulting in asthma.…”
Section: Discussionmentioning
confidence: 92%
“…We studied two phenotypes: asthma and IgE responsiveness dichotomized as high (> 100 kU/l) or low (≤ 100 kU/l) serum total IgE level [4,24]. Both the probands whose diagnosis could not be verified and the family members who reported asthma-like symptoms were classified as having an unknown phenotype.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the genes encoding the T helper 2-type cytokines (the interleukin genes IL3, IL4, IL5, IL9, and IL13), there are also other immunologically active genes such as those encoding interferon regulatory factor-1 (IRF1), colony-stimulating factor-2 (CSF2), and T-cell transcription factor-7 (TCF7). Several studies have reported suggestive linkage to atopy and high serum total immunoglobulin (Ig) E levels [1][2][3], bronchial hyperresponsiveness [4], and blood eosinophilia [5,6], and association to asthma [7], but so far the results have remained mutually inconclusive. An international effort was made to define the markers spanning the 5q cytokine cluster by linkage analysis in a total of 11 retrospectively pooled data sets (1037 A Second-Generation Association Study of the 5q31 Cytokine Gene Cluster and the Interleukin-4 Receptor in Asthma IL4R, located on chromosome 16p12, is exceptionally polymorphic.…”
Section: Introductionmentioning
confidence: 99%